2010
DOI: 10.1111/j.1365-2567.2009.03224.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of toll‐like receptor‐2, toll‐like receptor‐4, CD16 and human leucocyte antigen‐DR on peripheral blood monocytes during mild and severe dengue fever

Abstract: SummaryDengue fever (DF), a public health problem in tropical countries, may present severe clinical manifestations as result of increased vascular permeability and coagulation disorders. Dengue virus (DENV), detected in peripheral monocytes during acute disease and in in vitro infection, leads to cytokine production, indicating that virus-target cell interactions are relevant to pathogenesis. Here we investigated the in vitro and in vivo activation of human peripheral monocytes after DENV infection. ing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
84
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 57 publications
11
84
0
3
Order By: Relevance
“…Previous reports observed that CD16-expressing monocytes are increased in patients infected with DV compared with healthy individuals (53). We speculate that CD16 + monocytes may influence the pathogenesis of DV infection in additional ways beyond their role in triggering gd T cell responses.…”
Section: Discussionmentioning
confidence: 69%
“…Previous reports observed that CD16-expressing monocytes are increased in patients infected with DV compared with healthy individuals (53). We speculate that CD16 + monocytes may influence the pathogenesis of DV infection in additional ways beyond their role in triggering gd T cell responses.…”
Section: Discussionmentioning
confidence: 69%
“…For example, overexpression of TLR2 and TLR4 in monocytes of hepatitis B virus (HBV)-infected patients 49 and dengue virus-infected patients was reported. 50 However, down-modulation of TLR7 and TLR9 expression was reported in cells of HCV-or HBV-infected patients, which negatively correlated with viral load. 51,52 Together, these results suggest an important role of TLRs during viral infection.…”
mentioning
confidence: 99%
“…For example, overexpression of TLR2 and TLR4 in monocytes of hepatitis B virus (HBV)-infected patients 61 and Dengue virus-infected patients was reported. 62 However, down-modulation of TLR7 and TLR9 expression was reported in cells of hepatitis C virus-or HBV-infected patients, which negatively correlated with viral load. 63,64 Together, these results suggest an important role of TLRs during viral infection and that viruses can modulate their expression to avoid antiviral immunity or to promote pathogenic events with altered TLR expression and inflammatory immune response.…”
mentioning
confidence: 99%